2021
DOI: 10.5489/cuaj.7369
|View full text |Cite
|
Sign up to set email alerts
|

Inter-observer and intra-observer agreement of Bosniak classification of cystic renal masses: Comparison between original version to version 2019 and effect of an online support calculator

Abstract: Osman et al Original vs. 2019 version of Bosniak classification of cystic renal masses 2 © 2021 Canadian Urological Association MethodsThis IRB approved cross-sectional study evaluated 103 consecutively identified cystic (≤25% enhancing (1)) masses: 70.9% (73/103) with pathological confirmation (80.8% [59/73] malignant, 19.2% [14/73] benign), and 29.1% (30/103) Bosniak 2/2F masses classified by an expert genitourinary radiologist each with minimum 5 years stability on follow-up (1); the latter group added to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Previous studies have either demonstrated higher interobserver agreement with v2019 compared to v2005 or no significant difference. 16,[18][19][20][21][22] nevertheless, it must be stated that the inter-observer agreement rate remains low and is a concern going forward. For example, Yan et al quote a kappa ranging between 0.26 and 0.47 and Shampain et al report a gwet coefficient of 0.50.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have either demonstrated higher interobserver agreement with v2019 compared to v2005 or no significant difference. 16,[18][19][20][21][22] nevertheless, it must be stated that the inter-observer agreement rate remains low and is a concern going forward. For example, Yan et al quote a kappa ranging between 0.26 and 0.47 and Shampain et al report a gwet coefficient of 0.50.…”
Section: Discussionmentioning
confidence: 99%
“…25 Although its clinical impact and benefit of the inter-rater variability remain to be well-studied, the panel members believe that the v2019 classification is currently the preferred Bosniak classification. [26][27][28][29][30] Importantly, if there is disagreement or doubt regarding the classification of a complex renal cyst, it is the panel's opinion that such cases should be presented at a multidisciplinary meeting if this has the potential to alter management.…”
Section: █ Recommendationmentioning
confidence: 99%